Does Smoking Affect Outcome in Surgical Management of Ankle Arthritis? A COFAS Multicentre Study. Issue 1 (19th August 2016) - Mehta, Kinjal; Penner, Murray J.; Daniels, Timothy R.; Younger, Alastair S.; Wong, Hubert; Dryden, Peter; Wing, Kevin; Glazebrook, Mark A.
Category: Ankle Arthritis Introduction/Purpose: Smoking has been shown to increase complication rates after ankle surgery. The aim of this study was to compare complication rates between smokers and non smokers undergoing surgery for ankle arthritis. Methods: Smokers (n=88) and non smokers (n=565) with ankle arthritis who had undergone ankle arthrodesis or ankle arthroplasty were included in the study. Multicentre, prospective data was used from the COFAS ankle arthritis database. Patients with information available on smoking habits and 2 year follow up were included Results: There was no significant difference in the overall re operation rates between smokers and non smokers. However, the amputation rate was higher in smokers (3.4%) as compared to non smokers (0.7%). AOS scores and SF 36 scores were similar in the 2 groups. A higher proportion of smokers underwent fusion (46.5%) as compared to non smokers (28.8%). Amputation rate after ankle arthrodesis was higher in smokers (4.9%) as compared to non smokers (0.6%). Conclusion: Smokers have a higher amputation rate after ankle arthrodesis or ankle arthroplasty as compared to non smokers. Information from this study can be used during counselling of surgical patients